Advanced financial accounting : an international approach - Kothari, Jagdish; Barone, Elisabetta , 1970- (Financial Times Prentice Hall, 2011)
Today's enterprises are global in all respects - they trade globally and they raise capital in international markets. This title places an emphasis on interpretation, use and impact of standards in financial reporting